2021
DOI: 10.3389/fmed.2021.706689
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Burden and Determinants of Treatment Outcomes According to Age in Brazil: A Nationwide Study of 896,314 Cases Reported Between 2010 and 2019

Abstract: Approximately 1.4 million people die annually worldwide from tuberculosis. Large epidemiologic studies can identify determinants of unfavorable clinical outcomes according to age, which can guide public health policy implementation and clinical management to improve outcomes. We obtained data from the national tuberculosis case registry; data were reported to the Brazilian National Program (SINAN) between 2010 and 2019. Clinical and epidemiologic variables were compared between age groups (child: <10 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
2
9
0
Order By: Relevance
“…Thus, corroborated by the findings of other studies, our research also concludes that DOT is crucial for linking individuals to service and care 21 , 29 , 37 , 38 . During DOT, it is possible to diagnose the potential difficulties faced by patients, allowing for intervention when necessary 21 , thereby avoiding treatment dropout.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, corroborated by the findings of other studies, our research also concludes that DOT is crucial for linking individuals to service and care 21 , 29 , 37 , 38 . During DOT, it is possible to diagnose the potential difficulties faced by patients, allowing for intervention when necessary 21 , thereby avoiding treatment dropout.…”
Section: Discussionsupporting
confidence: 89%
“…The Ministry of Health considers DOT to be a minimum of three weekly observations by a healthcare professional on the patient’s medication intake during the whole treatment, totaling at least 24 doses in the intensive phase and 28 doses in the maintenance phase (under a standardized six-month treatment) 21 , 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence and comorbidity were not related; however, many factors have been shown to be associated with adherence to TB treatment, including patient characteristics, treatment regimens, and healthcare settings ( WHO, 2003 ). Previous systematic reviews and studies showed that diabetes and chronic renal failure lead to an increase in poor outcomes, particularly death, in patients with TB ( Baker et al, 2011 ; Baghaei et al, 2014 ; Barreto-Duarte et al, 2021 ). Interestingly, interstitial pulmonary disease is associated with adherence and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis remains an important public health problem throughout the world and Brazil is one of the 22 countries with high tuberculosis burdens identified by WHO (Barreto-Duarte et al, 2021). Nine studies analysed antiinfectives used for tuberculosis treatment, analysing predominantly pharmacogenes coding for drug metabolism enzymes (NAT2, CYP2E1, GSTT1) and outcomes of adverse events (Costa et al, 2012;Forestiero et al, 2013;Heinrich et al, 2016;Monteiro et al, 2012;Possuelo et al, 2008;Santos et al, 2013;Teixeira et al, 2011;Zaverucha-do-Valle et al, 2014), and drug effect of ABCB1 transporter (Pontual et al, 2017).…”
Section: Discussionmentioning
confidence: 99%